States, nations and the great powers the sources of regional war and peace - Miller, Benjamin 1953- (Cambridge studies in international relations, 2007)
Miller offers a theory of war and peace developed through an analysis of regional conflict. The book contains detailed data on the causes of war in the post-1945 era and of the state-to-nation balance in different regions.